2006
DOI: 10.4161/cc.5.17.3183
|View full text |Cite
|
Sign up to set email alerts
|

Histone Phosphorylation and Pericentromeric Histone Modifications in Oocyte Meiosis

Abstract: Epigenetic regulation of pericentromeric heterochromatin is crucial for proper interactions between kinetochores and spindle microtubules governing accurate chromosome segregation. Here, we first examined the dynamic distribution of phosphorylated serine 10 and 28 on H3 during mouse oocyte maturation and early embryo development using immunofluorescent staining and confocal microscopy. Our results revealed strong signals of phosphorylated H3/ser10 and 28 in the pericentromeric heterochromatin area and continuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 58 publications
4
46
0
Order By: Relevance
“…34 Interestingly, we found that inhibition of Aurora kinase significantly decreased the phosphorylation levels of both H3/ Ser10 and H3/Ser28 in mouse oocyte, resulting in chromosome misalignment. 31 These observations suggest that Aurora kinase participates in the regulation of histone H3 phosphorylation during oocyte meiosis, which may be essential for the correct chromosome alignment and segregation. On the other hand, the phosphatase that dephosphorylates H3/Ser10 has been identified as protein phosphasetase 1 (PP1) in budding yeast and nematodes.…”
Section: Functions Of Histone Modifications During Mammalian Oocyte Mmentioning
confidence: 97%
See 2 more Smart Citations
“…34 Interestingly, we found that inhibition of Aurora kinase significantly decreased the phosphorylation levels of both H3/ Ser10 and H3/Ser28 in mouse oocyte, resulting in chromosome misalignment. 31 These observations suggest that Aurora kinase participates in the regulation of histone H3 phosphorylation during oocyte meiosis, which may be essential for the correct chromosome alignment and segregation. On the other hand, the phosphatase that dephosphorylates H3/Ser10 has been identified as protein phosphasetase 1 (PP1) in budding yeast and nematodes.…”
Section: Functions Of Histone Modifications During Mammalian Oocyte Mmentioning
confidence: 97%
“…2). 31 At GV stage, staining of H3/Ser28ph was barely observed on chromatin. Upon meiotic resumption, H3/Ser28ph was clearly detectable at the periphery of Pre-MI chromosomes, and this distribution pattern was maintained until MII.…”
Section: Changes In Histone Modifications During Mammalian Oocyte Matmentioning
confidence: 99%
See 1 more Smart Citation
“…It gradually becomes phosphorylated on threonine 232 (Thr232) during oocyte maturation. Phosphorylation of AURKB activates this kinase and leads to the phosphorylation of histone H3 and the gradual condensation of chromatin (Jelinkova & Kubelka 2006, Wang et al 2006, Swain et al 2008. Moreover, altered AURKB activity increases the risk in chromosome congression failure, nondysjunction, and aneuploidy in mammalian oocytes (Vogt et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Posttranslational modifications such as acetylation, methylation, and phosphorylation regulate the DNA-binding property of histones including H3. In some mammalian species, phosphorylation of H3 by aurora kinase and an adjacent dimethylated lysine residue are coordinately involved in chromosomal condensation during oocyte maturation (Bui et al 2007;Ding et al 2011;Eberlin et al 2008;Gu et al 2008;Jelinkova and Kubelka 2006;Maton et al 2003;Swain et al 2007;Wang et al 2006). …”
Section: Histone H3mentioning
confidence: 99%